2018
DOI: 10.1089/cell.2018.0045
|View full text |Cite
|
Sign up to set email alerts
|

Suprachoroidal Adipose Tissue-Derived Mesenchymal Stem Cell Implantation in Patients with Dry-Type Age-Related Macular Degeneration and Stargardt's Macular Dystrophy: 6-Month Follow-Up Results of a Phase 2 Study

Abstract: This prospective clinical case series aimed to investigate the safety and efficacy of suprachoroidal adipose tissue-derived mesenchymal stem cell (ADMSC) implantation in patients with dry-type age-related macular degeneration (AMD) and Stargardt's macular dystrophy (SMD). This study included four patients with advanced-stage dry-type AMD and four patients with SMD who underwent suprachoroidal implantation of ADMSCs. The best-corrected visual acuity (BCVA) in the study was 20/200. The worse eye of the patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…The continuous improvement in this study through a 1‐year follow‐up could relate to this phenomenon. The choroidal thickening in the set of study patients could be the reflectance of an increase in choroidal perfusion compatible with previous study results (Oner et al, 2018; Oner, Gonen, Sevim, Sinim, Cetin, & Ozkul, 2019a; Oner, Gonen, Sevim, Sinim, & Unlu, 2019b). Their group also used umbilical cord‐derived MSCs (UC‐MSCs) as a stem cell source.…”
Section: Inherited Eye Diseases In Turkeysupporting
confidence: 90%
See 1 more Smart Citation
“…The continuous improvement in this study through a 1‐year follow‐up could relate to this phenomenon. The choroidal thickening in the set of study patients could be the reflectance of an increase in choroidal perfusion compatible with previous study results (Oner et al, 2018; Oner, Gonen, Sevim, Sinim, Cetin, & Ozkul, 2019a; Oner, Gonen, Sevim, Sinim, & Unlu, 2019b). Their group also used umbilical cord‐derived MSCs (UC‐MSCs) as a stem cell source.…”
Section: Inherited Eye Diseases In Turkeysupporting
confidence: 90%
“…Therefore, the subretinal delivery technique was abandoned and was replaced with the suprachoroidal delivery method which did not cause any complication other than a subconjunctival hemorrhage. The suprachoroidal delivery method being near the choroid also had the advantage of allowing the produced growth factors (GF) to enter the choroidal flow and reaching the endothelial cell receptors and eventually reaching to and interacting with retinal pigment epithelium cells (RPEs), Muller cells, and photoreceptors and managing to constant GF secretion in the choroidal flow (Oner, Gonen, Sevim, Sinim, & Unlu, 2018). The continuous improvement in this study through a 1‐year follow‐up could relate to this phenomenon.…”
Section: Inherited Eye Diseases In Turkeymentioning
confidence: 99%
“…In addition to the official clinical trial studies reported at http://www.clinicaltrials.gov , a number of other studies using cell replacement therapy for ABCA4 -associated retinopathy have been published. In one study, four subjects received a graft of adipose tissue-derived mesenchymal stem cells that was bilaterally delivered between the choroid and the sclera ( Oner et al, 2018 ). Improvements were found in visual performance as well as responses in multifocal ERG analyses, without any safety complications.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…MSCs are an inherently heterogeneous population of cells whose therapeutic potency varies with the characteristics of the donor, tissue of origin, isolation method, and in vitro preparation methods (e.g., cell culture protocol and scale-up). The common sources of MSCs for clinical trials of retinal degeneration therapy are bone marrow (BM) stem cells (Cotrim et al, 2017;Park et al, 2017), adipose-derived MSCs (ASC) (Oner et al, 2016(Oner et al, , 2018 and umbilical cord-derived MSCs (such as UC-MSC or palucorcel) (Heier et al, 2020). They differ in the ease and efficiency of harvesting, proliferative ability and senescence, and paracrine activities, which greatly affect their therapeutic potency (Fričová et al, 2020).…”
Section: Overcoming the Heterogeneity In The Msc Productmentioning
confidence: 99%